2013
DOI: 10.1002/hyp.9844
|View full text |Cite
|
Sign up to set email alerts
|

A simple temperature method for the estimation of evapotranspiration

Abstract: Accurate estimation of evapotranspiration (ET) is essential in water resources management and hydrological practices. Estimation of ET in areas, where adequate meteorological data are not available, is one of the challenges faced by water resource managers. Hence, a simplified approach, which is less data intensive, is crucial. The FAO‐56 Penman–Monteith (FAO‐56 PM) is a sole global standard method, but it requires numerous weather data for the estimation of reference ET. A new simple temperature method is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 11 publications
(12 reference statements)
2
25
0
Order By: Relevance
“…Sensitivity analysis is an important technique to improve the understanding of the dominant climatic variables in the estimation of ET 0 in an area of interest (Enku and Melesse 2014). Currently, the major approaches of investigating sensitivity include the sensitivity curve approach and the sensitivity coefficient approach.…”
Section: Methods For Sensitivity Analysismentioning
confidence: 99%
“…Sensitivity analysis is an important technique to improve the understanding of the dominant climatic variables in the estimation of ET 0 in an area of interest (Enku and Melesse 2014). Currently, the major approaches of investigating sensitivity include the sensitivity curve approach and the sensitivity coefficient approach.…”
Section: Methods For Sensitivity Analysismentioning
confidence: 99%
“…We found that the CFSR rainfall was similar but overestimated the observed rainfall and the CFSR rainfall was multiplied by of 0.8 as a correction. Daily evapotranspiration (ET) was estimated from daily maximum temperature data using the temperature method developed by Enku & Melesse (2014). The long time series daily maximum temperature was collected from the CFSR dataset.…”
Section: Datamentioning
confidence: 99%
“…Journal of Water Resource and Protection (MoWIE). Potential evapo-transpiration (PET) was estimated for both of the watersheds using the temperature method [14].…”
Section: Datamentioning
confidence: 99%